Low molecular weight heparin dosing regimens after total joint arthroplasty: a prospective, single-center, randomized, double-blind study - Jingjing Shang; Liangliang Wang; Jinhong Gong; Xinru Liu; Dan Su; Xindie Zhou; Yuji Wang (Journal of Orthopaedic Surgery and Research)
Abstract Background Low molecular weight heparin (LMWH) has been the standard treatment for preventing venous thromboembolism after total joint arthroplasty. However, the evidence supporting specific LMWH dosing regimens is limited. Objectives This study assessed the efficacy and safety of three enoxaparin dosing regimens to prevent venous thromboembolism. Methods Participants undergoing hip or knee replacement were randomly assigned to receive 20 mg of enoxaparin 6 h postoperatively (Group A), 40 mg 6 h postoperatively (Group B), or 40 mg 12 h postoperatively (Group C). The primary outcomes included thromboembolic and major bleeding events within 3 months, while the secondary outcomes comprised ecchymosis, wound exudation, drainage volume, allogeneic red blood cell transfusion, and first postoperative day hemoglobin levels. Results A total of 536 patients were analyzed. The occurrence of thromboembolic events was comparably low across all groups. Group C exhibited the lowest postoperative ecchymosis rate at 19.3%, significantly less than Group A (32.8%, p = 0.004) and Group B (37.7%, p < 0.001). Ecchymosis rates were about double in Group A and 1.5 times higher in Group B compared to Group C. Significant differences were also observed in 24-hour and total postoperative drainage volumes, with Group B having higher volumes than the other groups. Clinical trial registration This trial was prospectively registered at the China Clinical Trials Registry (registration date: November 14, 2021; registration number: ChiCTR2100053191). Conclusion No significant differences in venous thromboembolism rates were seen between the tested enoxaparin dosing regimens after total joint arthroplasty. The 40 mg dose administered 12 h after surgery was associated with reduced postoperative ecchymosis and drainage volumes without an increased thrombosis risk, suggesting it is a safer and more effective option than earlier or lower dosages. Graphical Abstract